Pengaruh Strategi Directed Reading Thinking ActivityTerhadap Keterampilan Membaca PemahamanTeks Biografi Siswa Kelas X SMA Negeri 1 Matur - Rani Oktavia; Afnita Afnita (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
This study aims to determine whether there is an effect before using DRTA on the reading comprehension skills of class X SMA Negeri 1 Matur students and after using the DRTA strategy in reading comprehension skills of class X SMA Negeri 1 Matur students. This research is a quasi-experimental research with a research design that uses the One Group Pretest-Posttest design. The population in this study were students of class X SMA Negeri 1 Matur. Samples were taken using purposive sampling technique. The data of this research is the value of reading comprehension skills of tenth graders of SMA Negeri 1 Matur before and after using the DRTA strategy. Data were analyzed by t-test. The results of this study indicate that there is an effect before and after using the DRTA strategy in reading comprehension skills of class X students of SMA Negeri 1 Matur, namely tcount > ttable (3,52>1,71). The average reading comprehension ability of tenth graders of SMA Negeri 1 Matur after using the DRTA strategy was higher than before (94,87>47,37). Thus it can be concluded that the DRTA strategy has a significant effect on the reading comprehension skills of class X students of SMA Negeri 1 Matur.